Management Innovation and Leadership: The Moderating Role of Organizational Size - Vaccaro, Ignacio G.; Jansen, Justin J. P.; Van Den Bosch, Frans A. J.; Volberda, Henk W. (Journal of Management Studies, 2012)
abstractRecent research on management innovation, i.e. new managerial processes, practices, or structures that change the nature of managerial work, suggests it can be an important source of competitive advantage. In this study, we focus on management innovation at the organization level and investigate the role of leadership behaviour as a key antecedent. Due to its prominent role within organizations, top management has the ability to greatly influence management innovation. In particular, we focus on leadership behaviour and examine transformational and transactional leadership. Additionally, as contextual variables like organizational size may influence the impact of leadership, we investigate its moderating role. Findings show that both leadership behaviours contribute to management innovation. Interestingly, our study indicates that smaller, less complex, organizations benefit more from transactional leadership in realizing management innovation. On the other hand, larger organizations need to draw on transformational leaders to compensate for their complexity and allow management innovation to flourish.